The Effect of the Gymball Method on the Acceleration of Stage II Labor at the Mananggu Community Health Center - Sofya Alamri; Tut Rayani Aksohini Wijayanti (Calory Journal Medical Laboratory Journal, 2025)
Background: The second stage of labor is a critical phase associated with risks of maternal and neonatal complications if it lasts too long. Nonpharmacological interventions such as the gymball method have the potential to accelerate labor progress by optimizing the position and mobilization of the mother in labor, but contextual evidence in primary health care facilities in Indonesia is still limited. Objective: This study aims to analyze the effect of the gymball method on accelerating the second stage of labor in laboring mothers at the Mananggu Community Health Center. Methods: This study used a quasi-experimental design with a posttest-only control group approach. The sample consisted of 30 laboring women divided into an intervention group (gymball) and a control group (standard care). The dependent variable was the duration of the second stage of labor. Data were collected using observation sheets and partographs, then analyzed using an independent t-test. Results: The average duration of the second stage of labor in the gymball group was significantly shorter than that in the control group (p < 0.05). Conclusion: The gymball method was proven to be effective in accelerating the second stage of labor. This intervention is safe, low-cost, and feasible to be implemented as part of midwifery care at community health centers to improve the quality of normal delivery services.